Regulation of l-Alanine Dehydrogenase in Rhizobium leguminosarum bv. viciae and Its Role in Pea Nodules - Lodwig, Emma (American Society for Microbiology, 2004)
Alanine dehydrogenase (AldA) is the principal enzyme with which pea bacteroids synthesize alanine de novo. In free-living culture, AldA activity is induced by carboxylic acids (succinate, malate, and pyruvate), although the best inducer is alanine. Measurement of the intracellular concentration of alanine showed that AldA contributes to net alanine synthesis in laboratory cultures. Divergently transcribed from aldA is an AsnC type regulator, aldR. Mutation of aldR prevents induction of AldA activity. Plasmid-borne gusA fusions showed that aldR is required for transcription of both aldA and aldR; hence, AldR is autoregulatory. However, plasmid fusions containing the aldA-aldR intergenic region could apparently titrate out AldR, sometimes resulting in a complete loss of AldA enzyme activity. Therefore, integrated aldR::gusA and aldA::gusA fusions, as well as Northern blotting, were used to confirm the induction of aldA activity. Both aldA and aldR were expressed in the II/III interzone and zone III of pea nodules. Overexpression of aldA in bacteroids did not alter the ability of pea plants to fix nitrogen, as measured by acetylene reduction, but caused a large reduction in the size and dry weight of plants. This suggests that overexpression of aldA impairs the ability of bacteroids to donate fixed nitrogen that the plant can productively assimilate. We propose that the role of AldA may be to balance the alanine level for optimal functioning of bacteroid metabolism rather than to synthesize alanine as the sole product of N(2) reduction.